2022
DOI: 10.1186/s13024-022-00523-1
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease – the journey of a healthy brain into organ failure

Abstract: As the most common dementia, Alzheimer’s disease (AD) exacts an immense personal, societal, and economic toll. AD was first described at the neuropathological level in the early 1900s. Today, we have mechanistic insight into select aspects of AD pathogenesis and have the ability to clinically detect and diagnose AD and underlying AD pathologies in living patients. These insights demonstrate that AD is a complex, insidious, degenerative proteinopathy triggered by Aβ aggregate formation. Over time Aβ pathology d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 271 publications
0
56
0
3
Order By: Relevance
“…Since iPSC reprogramming rejuvenates cells and erases donor aging signatures, concerns were raised about the ability to model age-related diseases with iPSC-derived neuronal cultures [59]. It is well-established that AD develops over decades [60]. Thus, genetic factors may produce endophenotypes early in life; therefore, they can be captured in iPSC-derived neural cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since iPSC reprogramming rejuvenates cells and erases donor aging signatures, concerns were raised about the ability to model age-related diseases with iPSC-derived neuronal cultures [59]. It is well-established that AD develops over decades [60]. Thus, genetic factors may produce endophenotypes early in life; therefore, they can be captured in iPSC-derived neural cultures.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that AD develops over decades [60]. Thus, genetic factors may produce endophenotypes early in life; therefore, they can be captured in iPSC-derived neural cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This pathology has come to be associated with aberrant metabolism of the amyloid precursor protein (APP) [30]. These findings have led to the amyloid cascade hypothesis, in which an imbalance between production and clearance of Aβ peptides initiates the complex pathological cascade of AD [31,32]. A variant of the cascade view is the amyloid-β oligomer (AβO) hypothesis, which postulates that the brain damage of AD is instigated by toxic soluble amyloid oligomers Tyler and Tyler Natural Products and Bioprospecting (2022) 12:34 [33].…”
Section: The Amyloid Hypothesismentioning
confidence: 99%
“…In general, heart failure is commonly treated with HF-related medications and many of them have been reported to have protective effects on cognitive decline and AD ( Barthold et al, 2020 ; Poly et al, 2020 ; Nguyen et al, 2022 ; Olmastroni et al, 2022 ). Additionally, it is widely reported that AD pathology might begin 20 years before the clinical diagnosis of AD (e.g., Figure 1; Golde, 2022 ). Thus, patients of HF may have less chance to develop late-onset AD because HF is a leading cause of short survival in many western populations.…”
Section: Introductionmentioning
confidence: 99%